The development and standardization of Self-assessment for Hearing Screening of the Elderly - Kim G (Dove Medical Press, 2016)
Gibbeum Kim,1 Wondo Na,1 Gungu Kim,1 Woojae Han,2 Jinsook Kim2 1Department of Speech Pathology and Audiology, Hallym University Graduate School, Chuncheon, Republic of Korea; 2Division of Speech Pathology and Audiology, Research Institute of Audiology and Speech Pathology, College of Natural Sciences, Hallym Universtiy, Chuncheon, Republic of Korea Purpose: The present study aimed to develop and standardize a screening tool for elderly people who wish to check for themselves their level of hearing loss. Methods: The Self-assessment for Hearing Screening of the Elderly (SHSE) consisted of 20 questions based on the characteristics of presbycusis using a five-point scale: seven questions covered general issues related to sensorineural hearing loss, seven covered hearing difficulty under distracting listening conditions, two covered hearing difficulty with fast-rated speech, and four covered the working memory function during communication. To standardize SHSE, 83 elderly participants took part in the study: 25 with normal hearing, and 22, 23, and 13 with mild, moderate, and moderate-to-severe sensorineural hearing loss, respectively, according to their hearing sensitivity. All were retested 3 weeks later using the same questionnaire to confirm its reliability. In addition, validity was assessed using various hearing tests such as a sentence test with background noise, a time-compressed speech test, and a digit span test. Results: SHSE and its subcategories showed good internal consistency. SHSE and its subcategories demonstrated high test–retest reliability. A high correlation was observed between the total scores and pure-tone thresholds, which indicated gradually increased SHSE scores of 42.24%, 55.27%, 66.61%, and 78.15% for normal hearing, mild, moderate, and moderate-to-severe groups, respectively. With regard to construct validity, SHSE showed a high negative correlation with speech perception scores in noise and a moderate negative correlation with scores of time-compressed speech perception. However, there was no statistical correlation between digit span results and either the SHSE total or its subcategories. A confirmatory factor analysis supported three factors in SHSE. Conclusion: We found that the developed SHSE had valuable internal consistency, test–retest reliability, and convergent and construct validity. These results suggest that SHSE is a reliable and valid measure to represent the degree of hearing loss in the elderly. Keywords: hearing screening, self-assessment, questionnaire, presbycusis, aging